PERAN PEMIMPIN DALAM PELAYANAN PUBLIK DI KANTOR CAMAT XIII KOTA KAMPAR KABUPATEN KAMPAR - hernimawati, hernimawati; sudaryanto, sudaryanto (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
District XIII Kampar City is one of the districts in Kampar regency. The number of sub-districts in Kabupaten Kampar reaches 21 districts. District XIII Koto Kampar consists of 13 villages that have various potentials that can be developed and economic value. Like Muara Takus temple located in Muara Takus village, Salai Patin processing in Desa Mosque and Pulo Simo Waterfall in Tanjung Alai Village.All these potentials are very proud for the Government and the people of District XIII Kampar City. It's just that this has not been managed with the maximum. This is evidenced by inadequate road access to reach the site.Therefore, the role of leaders needed to overcome them. According Sinambela (2014), the role of leaders in public services is to provide motivation, create a pleasant atmosphere, coordinate and implement the policy. From the results of the research, the District Leader XIII Koto Kampar has performed its role well. Where Sub District as a Local Government Apparatus District is the spearhead of the implementation of government. Whereas the sub-district with the number of apparatus that has not been complete and supported with the existing agency. The Camat office is a government, development and community administrator supported by the agency office, the sub-district administration is led by a subdistrict head who is in charge of the government with the help of the staff of the Kecamatan Office and the existing department in the sub-district and the village administration.